Van der Woude and Popliteal Pterygium Syndromes: Broad intrafamilial variability in a three generation family with mutation in IRF6. Issue 9 (10th June 2016) - Busche, Andreas; Hehr, Ute; Sieg, Peter; Gillessen‐Kaesbach, Gabriele
Abstract : Patients with Van der Woude syndrome typically present with cleft lip, cleft lip and palate, or with cleft palate only. In contrast to non‐syndromic cleft lip and/or palate, Van der Woude syndrome typically is characterized by bilateral, paramedian lower‐lip pits. Popliteal pterygium syndrome shares features with Van der Woude syndrome, but, in addition, is characterized by a popliteal pterygium, genital anomalies, cutaneous syndactyly of the fingers and the toes, and a characteristic pyramidal fold of skin overlying the nail of the hallux. In some patients oral synechiae or eyelid synechiae are present. Van der Woude Syndrome and Popliteal pterygium syndrome are autosomal dominantly inherited disorders caused by heterozygous mutations in IRF6 . We present a three generation family with tremendous intrafamilial phenotypic variability. The newborn index patient had a diagnosis of Popliteal pterygium syndrome. The mother presented with a classic Van der Woude Syndrome, while the maternal grandfather had Van der Woude Syndrome as well as minor signs of Popliteal pterygium syndrome. In all three affecteds the known pathogenic mutation c.265A>G, p.Lys89Glu in IRF6 was identified. While inter‐ as well as intra‐familial variability has been described in IRF6 ‐related disorders, the occurrence of a typical Van der Woude Syndrome without any other anomalies as well as a diagnosis of Popliteal pterygium syndrome in the same family is rare. © 2016 Wiley Periodicals, Inc.